Prevalensi Kualitas Tidur Keluarga di Ruang Rawat Inap RS Izza Karawang di Masa Pandemi Covid-19 - Zevi Agus Mulyana; Amzal Mortin Andas; Puji Astuti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The accompanying family of patients who are hospitalized is at risk of experiencing poor sleep quality. The impact of poor sleep quality can affect mood, ineffective communication with doctors or nurses, and interfere with the ability to make decisions and care. The purpose of the study was to determine the prevalence of family sleep quality levels in inpatient rooms during the pandemic. The design of this research is descriptive-analytic with a cross-sectional approach. The study population was the entire family of patients who were treated in an inpatient room during the pandemic, using a consecutive sampling technique with a sample of 53 respondents. Researchers maintain confidentiality, provide fairness and explain the purpose and benefits of research to respondents. This study used univariate analysis. The results were the majority who experienced adequate sleep quality 53 respondents (53.2%), bad quality 31 respondents (32.3%), and good quality 12 respondents (12.5%). The conclusion shows that the patient's family experienced adequate sleep quality. Future researchers are expected to examine factors related to family sleep quality in different places such as the Intensive Care Unit (ICU).